Plasmodium LCCL domain-containing modular proteins have their origins in the ancestral alveolate - Callum De Hoest-Thompson; Virginia Marugan-Hernandez; Johannes T. Dessens (Open Biology, 2024)
Plasmodium species encode a unique set of six modular proteins named LCCL lectin domain adhesive-like proteins (LAPs) that operate as a complex and that are essential for malaria parasite transmission from mosquito to vertebrate. LAPs possess complex architectures obtained through unique assemblies of conserved domains associated with lipid, protein and carbohydrate interactions, including the name-defining LCCL domain. Here, we assessed the prevalence of Plasmodium LAP orthologues across eukaryotic life. Our findings show orthologous conservation in all apicomplexans, with lineage-specific repertoires acquired through differential lap gene loss and duplication. Besides Apicomplexa, LAPs are found in their closest relatives: the photosynthetic chromerids, which encode the broadest repertoire including a novel membrane-bound LCCL protein. LAPs are notably absent from other alveolate lineages (dinoflagellates, perkinsids and ciliates), but are encoded by predatory colponemids, a sister group to the alveolates. These results reveal that the LAPs are much older than previously thought and pre-date not only the Apicomplexa but the Alveolata altogether.